Children's right to participation in residential care: A staff-based study in Portugal - Magalhães, E. (2025)
Background Youth in residential care (RC) reveal high-risk trajectories, which require upholding their rights and providing them with opportunities to participate. Objective We aimed to identify staff profiles focused on their perceptions of participation and the association with sociodemographic variables. Participants and setting This study included quantitative analysis of qualitative data collected from 87 professionals in the RC (Mage = 38.92, SD = 9.36). Methods A variable-centered approach was applied to identify the associations between the categories and configurations of profiles, followed by a person-centered approach to group professionals who shared similar conceptual profiles. Results Three profiles were identified. The Full Participation profile (14.9 %) involves those who conceive participation as ensuring that youth's views must be acted upon, and youth should participate in their education, play activities and RC issues to promote their empowerment. This cluster did not include participants from settings only for females, showing a greater proportion of males-only settings than the others. The Participation in the Case Plan profile described most professionals (56.3 %), reporting that youth should participate in child protection cases and family contacts to foster their well-being and quality of RC. This cluster showed a greater proportion of female-only settings than did the others. The Blurred Participation profile (28.7 %) represented a non-specific vision of how participation might work and showed a greater proportion of mixed settings than others. Conclusions Most professionals focused on youth participation in case plans more than on their capacity to participate in all decisions and be empowered. Skilled professionals are required to encourage participation in RC.